A cross-cultural comparative study of internal auditor skills: UK vs Korea. Issue 3 (11th September 2017) - Seol, Inshik; Sarkis, Joseph; Wang, Zhihong (Rita)
Abstract : Purpose: Based on the theoretical development by House et al. (2004), the purpose of this paper is to investigate the cross-cultural differences of internal auditors' perceptions on the importance of internal auditor skills. Design/methodology/approach: The authors developed a survey based on the competency framework for internal auditing and collected data from the UK (Anglo cultural cluster) and Korea (Confucian cultural cluster). In total, 231 internal auditors participated in the study. Findings: The results showed that UK auditors perceived behavioral skills as more important than cognitive skills, while Korean auditors had an opposite perception. Not surprisingly, UK auditors rated each sub-category of behavioral skills higher than Korean auditors; Korean auditors gave higher scores than UK auditors for each sub-category of cognitive skills. Research limitations/implications: One limitation of the study is that two different data collection methods were used for the study: online for the UK and paper-based for Korean auditors. Another limitation of the study is that the authors did not analyze the possible impact of each participating auditor's background knowledge. Practical implications: The findings of the study contributes to professional practice by providing culturally adaptive criteria for regulators' policy-making, organizations' employee hiring and training, and educators' curriculum design across various cultural environments. Originality/value: The findings of the study can provide some insights on cultural impacts to help academic researchers develop models regarding the internal auditor selection and training in different nations.